Rule-Based Reasoning Penentuan Pola Asuh Anak Berbasis Aplikasi Android - Ali Syarifuddin; Muhammad Fauzan Azima; Siti Nur Laila (JURNAL TECNOSCIENZA, 2026)
Parenting style plays a crucial role in shaping children’s character and behavior. However, limited access to relevant knowledge often prevents parents from recognizing the type of parenting they practice. To address this issue, this study developed an Android-based application for determining parenting styles using the Scrum software development framework. The parenting style classification system was built by applying the Rule-Based Reasoning (RBR) method, which processed Pengguna questionnaire inputs into IF–THEN logical rules based on two primary psychological dimensions: control and warmth. The rules and assessment indicators were derived from expert knowledge obtained from Gantari Psychology Clinic. Based on the scores of these two dimensions, the system classified parenting styles into four categories: Authoritative (Democratic), Authoritarian, Permissive, and Neglectful. In addition, the application provided personalized parenting recommendations tailored to the child’s age (0–60 months) and the dominant parenting style identified. Functional testing of the system used the Black Box Testing method indicated that all core features operate effectively and in accordance with the system design. This application was expected to serve as a practical self-learning tool for parents to evaluate and improve their parenting practices, thereby supporting optimal child development.